Program Penguatan Ketahanan Pangan, Pengelolaan Sampah, Air dan Sanitasi Guna Mewujudkan Kampung Iklim Kelurahan Tugurejo - Muhammad Abbi Fahrezy Sutikno; Dwi Rahmawati; Yonika Sindiana Prahmani; Amnan Haris; Tiara Dwi Wulandari; Desy Fitria Astutianingtyas (Yayasan Keluarga Guru Mandiri, 2023)
Tugurejo Village is one of the sub-districts in Semarang City which directly borders the Java Sea, which is located in the western part of the Semarang City area. Tugu District, with its supportive location, has great potential for the growth and development of new buildings as part of the regional development process. However, this growth also carries risks, especially related to changes in land use which can increase the potential for disasters. Community service with the aim of increasing the activities of the Tugurejo Village climate village program. Methods for collecting data and formulating programs qualitatively through documentation, observation, Focus Group Discussion, questionnaires and structured interviews. The four programs were successfully developed, including urban farming, urban aquaculture, rainwater harvesting and waste bank programs.